A tale of two institutions : the ARF, ADMM-plus and security regionalism in the Asia Pacific - Tan, See Seng (2019)
The Asia-Pacific region is served by not one but two region-wide security arrangements, namely, the ASEAN Regional Forum (ARF) and its newer counterpart, the ASEAN Defence Ministers’ MeetingPlus (ADMM-Plus). Like their namesake and appointed custodian, the Association of Southeast Asian Nations (ASEAN), both the ARF and ADMM-Plus lack the deeply institutionalized character of their Western counterparts and are not deemed as particularly effective mechanisms for conflict management and resolution. On the other hand, (and, importantly, regional aspirations aside), the institutional designs of the ARF and ADMM-Plus as principally mechanisms for dialogue and consultation essentially mean they are not created to facilitate ambitious forms of security cooperation, although theoretically they could evolve in the future and assume more complex and challenging responsibilities.1